Implementasi Strategi Bersaing BPRS Fadhilah dalam Meningkatkan Jumlah Nasabah Produk Tabungan Wadi’ah Menggunakan Porter Five Forces dan SWOT Analisis - Tiwi Suvia; Yosy Arisandi; Katra Pramadeka (Universitas Muhammadiyah Surabaya, 2026)
The purpose of this study is to examine the implementation of competitive strategies of BPRS Fadhilah Bengkulu in increasing the number of customers of the wadi’ah savings product and to analyze the competitive environment using the Porter Five Forces approach and SWOT analysis. This research employs a descriptive qualitative approach with a field research method. The results show that the competitive strategy implemented by BPRS Fadhilah Bengkulu is carried out through improving service quality, implementing pick-up service, and offering savings products with affordable initial deposits and no monthly administrative fees. Based on the Porter Five Forces analysis, competition among Islamic financial institutions offering similar savings products is relatively intense. The threat of new entrants mainly comes from technology-based financial institutions; however, BPRS Fadhilah responds by prioritizing excellent service and direct interaction with customers. The bargaining power of customers in obtaining high-quality services encourages the bank to improve service quality and accessibility. The threat of substitute products comes from digital financial services, while the role of third parties (shareholders) supports the operational stability of the bank through financial support. Meanwhile, the SWOT analysis indicates that strengths lie in service convenience and the application of Islamic principles, weaknesses are related to limited facilities and public understanding, opportunities arise from payroll cooperation and promotion through social media, while threats come from increasing competition among financial institutions and the development of banking technology.